Expression of Lon-like Protease Gene from Lactobacillus plantarum IIA-1A5 in Escherichia coli BL21(DE3) - Olfa Mega; Cece Sumantri; Irma Isnafia Arief; Cahyo Budiman (Agricultural Faculty, 2019)
Proteases are one of most important and abundant enzymes produced by the biotechnology industry, for scientific, physiological and industrial application and dominates of the whole enzyme market. Lactobacillus plantarum IIA-1A5 is an Indonesian lactic acid bacteria (LAB) isolated from beef Peranakan Ongole cattle. Preliminary analysis on its whole genome sequence indicated that this strain harbours some genes involved in protein degradation and might be promising to be further applied. This study aims to optimize the gene sequence of a lon-like protease of L. plantarum IIA-1A5 for heterologous expression system. The Lon-like gene expression system is made using genes that have been optimized first in silico. pET-28a(+), E. coli BL21(DE3), Nde1 and BamH1 were used in this study as a expression vector, a host and retriction enzyme, respectively. Molecular weight was validated using SDS-PAGE and expasy.org software. The results showed that optimization increased codon adaptation index value (CAI) and GC content to 0.97 and 56.57%, respectively, which were suitable for the E. coli expression system. The Lon-like IIA gene was successfully expressed in the cell cytoplasm by induction of 1 mM Isopropyl -D-1-thiogalactopyranoside (IPTG) at 37 C. As many as 88% of Lon-like IIA codons were distributed in the 91-100 quality group. Lon-like IIA was successfully expressed in a host cell induced with 1 mM IPTG at 37oC . IPTG induction was performed at the 3rd hour of incubation with OD600 0.59. In addition, Lon-like IIA molecular weight was detected approximately 43 kDa.